2017
DOI: 10.1093/molbev/msx213
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Regional Variation in Selection Intensity within Protein-Coding Genes Using DNA Sequence Polymorphism and Divergence

Abstract: Numerous approaches have been developed to infer natural selection based on the comparison of polymorphism within species and divergence between species. These methods are especially powerful for the detection of uniform selection operating across a gene. However, empirical analyses have demonstrated that regions of protein-coding genes exhibiting clusters of amino acid substitutions are subject to different levels of selection relative to other regions of the same gene. To quantify this heterogeneity of selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…To compare relationships of positive selection to phylogenetic support more broadly across Zan and other molecular markers, we constructed individual Bayesian phylogenies and performed corresponding PAML selection analyses for all reliable sequences of all eutherian genes (n = 40) previously shown to have evolved by positive selection (as of June 2022; [47,51,[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83]). Annotated gene functions ranged from reproduction (n = 23) to sensory perception (n = 7), immunity (n = 5), metabolism (n = 3), the nervous system (n = 1), and the cell cycle (n = 1), and the genes' compared sequence lengths ranged from 394 nt (for S100a2) to 8016 (for Cr2) nt (Table 1), collectively encompassing >104,000 nt of gene coding sequence.…”
Section: Testing the Phylogenetic Utility Of Zanmentioning
confidence: 99%
“…To compare relationships of positive selection to phylogenetic support more broadly across Zan and other molecular markers, we constructed individual Bayesian phylogenies and performed corresponding PAML selection analyses for all reliable sequences of all eutherian genes (n = 40) previously shown to have evolved by positive selection (as of June 2022; [47,51,[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83]). Annotated gene functions ranged from reproduction (n = 23) to sensory perception (n = 7), immunity (n = 5), metabolism (n = 3), the nervous system (n = 1), and the cell cycle (n = 1), and the genes' compared sequence lengths ranged from 394 nt (for S100a2) to 8016 (for Cr2) nt (Table 1), collectively encompassing >104,000 nt of gene coding sequence.…”
Section: Testing the Phylogenetic Utility Of Zanmentioning
confidence: 99%
“…To assess relationships of positive selection to phylogenetic support more broadly, we retrieved all reliable sequences of all genes previously shown to have evolved by positive selection [24,91,95,100,[107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122] and conducted Bayesian and selection analyses on individually constructed gene trees. Excluding 12 genes with too little taxonomic representation (either fewer than nine Orders total or no basal Orders), the analysis yielded Bayesian (>95% posterior support) and M7 and M8 model selection data (magnitude = dN/dS = ω, and frequency= f) for 40 positively selected genes with widely ranging functions, including 23 genes that function in reproduction, seven in sensory perception, five in immunity, three in metabolism, and one each in the nervous system and the cell cycle.…”
Section: Divergence Comparisonsmentioning
confidence: 99%
“…(2) If population sequence data that spans multiple time points is available then it is possible to identify positively selected sites by assessing the change in mutant frequency over time (Henn et al 2012;Foll et al 2014). (3) More recently it has been demonstrated that it is possible to determine nucleotide sites under selection by analyzing the distribution of those sites across a gene (Zhang, Townsend 2009;Zhao et al 2017).…”
Section: Introductionmentioning
confidence: 99%